Estudo da incorporação de cascalho proveniente da perfuração de poços de petróleo em formulações para tijolos de solo-cimento - Marques, Sheyla Karolina Justino (2011)
The present work is to study the characteristics and technological properties of soil-cement bricks made from binary and ternary mixtures of Portland cement, sand, water, with or without addition of gravel from the drilling of oil wells, which could be used by industry, aiming to improve its performance and reduce cost by using the residue and, consequently, increasing its useful life. The soil-cement bricks are one of the alternatives to masonry construction. These elements, after a short curing period, provide compressive strength similar to that of solid bricks and ceramic blocks, and the higher the resistance the higher the amount of cement used. We used the soil from the city of São José do Mipibu / RN, the banks of the River Baldun, cement CPIIZ-32 and residue of drill cuttings from oil wells drilling onshore wells in the town of Mossley, RN, provided Petrobras. To determine the optimum mix, we studied the inclusion of different residues (100%, 80%, 70%, 60% and 50%) where 15 bodies were made of the test piece. The assessment was made of bricks made from simple compression tests, mass loss by immersion and water absorption. The experimental results proved the efficiency and high utilization of the waste from the drilling of oil wells, making the brick-cement-soil residue with a higher strength and lower water absorption. The best result in terms of mechanical strength and water absorption for the ternary mixture was 10% soil, 14% cement and 80% residue. In terms of binary mixtures, we obtained the best result for the mix-cement residue, which was 14% cement incorporated in the residue